Studies of the Structure and Optical Properties of BaSrMgWO6 Thin Films Deposited by a Spin-Coating Method - Luciana Punga; Abderrahman Abbassi; Mihaela Toma; Teodor Alupului; Corneliu Doroftei; Marius Dobromir; Daniel Timpu; Florica Doroftei; Laura Hrostea; George G. Rusu; Abdelati Razouk; Felicia Iacomi (Nanomaterials, 2022)
Highly transparent thin films with the chemical formula BaSrMgWO6 were deposited by spin coating using a solution of nitrates of Ba, Sr, and Mg and ammonium paratungstate in dimethylformamide with a Ba:Sr:Mg:W ratio = 1:1:1:1. XRD, SEM, EDX, and XPS investigations evidenced that annealing at 800 °C for 1 h results in an amorphous structure having a precipitate on its surface, and that supplementary annealing at 850 °C for 45 min forms a nanocrystalline structure and dissolves a portion of the precipitates. A textured double perovskite cubic structure (61.9%) was found, decorated with tetragonal and cubic impurity phases (12.7%), such as BaO2, SrO2, and MgO, and an under-stoichiometric phase (24.4%) with the chemical formula Ba2−(x+y) SrxMgyWO5. From transmittance measurements, the values of the optical band gap were estimated for the amorphous (Egdir = 5.21 eV, Egind = 3.85 eV) and nanocrystalline (Egdir = 4.69 eV, Egind = 3.77 eV) phases. The presence of a lattice disorder was indicated by the high Urbach energy values and weak absorption tail energies. A decrease in their values was observed and attributed to the crystallization process, lattice strain diminution, and cation redistribution.